The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3389/fonc.2021.756334
|View full text |Cite
|
Sign up to set email alerts
|

A New Antitumor Direction: Tumor-Specific Endothelial Cells

Abstract: Targeting tumor blood vessels is an important strategy for tumor therapies. At present, antiangiogenic drugs are known to have significant clinical effects, but severe drug resistance and side effects also occur. Therefore, new specific targets for tumor and new treatment methods must be developed. Tumor-specific endothelial cells (TECs) are the main targets of antiangiogenic therapy. This review summarizes the differences between TECs and normal endothelial cells, assesses the heterogeneity of TECs, compares … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 147 publications
(141 reference statements)
0
5
0
Order By: Relevance
“…Endothelial barrier function is important in maintaining the proper functioning of the circulatory system and preventing the infiltration of harmful substances into tissues ( Mehta and Malik, 2006 ; Stan, 2007 ). It also plays a critical role in preventing cancer metastasis ( Chen et al, 2013 ; Wettschureck et al, 2019 ; Liang et al, 2021 ). EC barrier function is maintained by cellular junctions between adjacent ECs, which limit the movement of substances through the intercellular spaces ( Dejana et al, 2008 ).…”
Section: Resultsmentioning
confidence: 99%
“…Endothelial barrier function is important in maintaining the proper functioning of the circulatory system and preventing the infiltration of harmful substances into tissues ( Mehta and Malik, 2006 ; Stan, 2007 ). It also plays a critical role in preventing cancer metastasis ( Chen et al, 2013 ; Wettschureck et al, 2019 ; Liang et al, 2021 ). EC barrier function is maintained by cellular junctions between adjacent ECs, which limit the movement of substances through the intercellular spaces ( Dejana et al, 2008 ).…”
Section: Resultsmentioning
confidence: 99%
“…Since stromal [7] and endothelial [30] cells, present in the BM, have previously been described to confer resistance to therapy, U937 cells were cultured on M-MΦ, fibroblasts (HS-5) or endothelial cell (EA.hy926) monolayers (Fig. 1D).…”
Section: Mif Inhibition Induces Aml Blast Apoptosis But Bm Cells Are ...mentioning
confidence: 99%
“…Suprabasin, an upstream component of the AKT pathway, was substantially expressed in TECs compared to normal ECs and linked favourably with TECs’ capacity for migration and tube formation ( 75 ). On the other hand, microarray and immunohistochemical studies revealed that biglycan is a specific marker of TEC and an autocrine angiogenic factor of TECs ( 76 ). Because of the aggressive behaviour of tumor endothelial cells and their particular molecular, cytogenetic, and metabolic characteristics, the tumor microenvironment can therefore selectively draw in immune suppressive cells.…”
Section: Endothelial Cells In Tumors Are the “Switch Point” Aren’t They?mentioning
confidence: 99%
“…EndMT induced by TGF-β shows a decrease in the expression of endothelial markers such as VE-cadherin, claudin and zona-occludens 1 (ZO-1) and an elevation in EMT transcription factors such as Snail, Slug and ZEB-1 which marks metastasis. TGF-β promotes ECs to change into CAF-like cells, which results in the loss of endothelial adhesion molecules and remodelling of the endothelium cytoskeleton via the Rho and Rac-1 signalling pathway, which is the primary characteristic of EndMT ( 76 , 137 , 138 ). It has been found that hypoxia associated with inflammation or tissue damage can also cause EndEMT ( 139 ).…”
Section: Trans-endothelial Migrationmentioning
confidence: 99%